1990
DOI: 10.1007/bf00219969
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic effect of carbon monoxide on the heart

Abstract: The acute effects of carbon monoxide (CO) on cardiac metabolism at the mitochondrial level were investigated. Rats were exposed to 4% CO for 4 minutes in a closed chamber. Immediately after exposure, hearts were removed and frozen with a precooled clamp. Blood from the thoracic cavity was sampled for analysis. Gas analysis of arterial blood taken from the abdominal aorta demonstrated severe hypoxia with oxygen partial pressure less than 20 mmHg, metabolic acidosis and reduced pH value. There were no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Thus, induction of iNOS mRNA in macrophages and hepatocytes requires ongoing protein synthesis. In contrast, we recently reported that CHX actually induces iNOS mRNA in rat vascular smooth muscle cells (VSM) (19). Additionally, the induction of iNOS mRNA by LPS is substantially potentiated by CHX in VSM (19).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, induction of iNOS mRNA in macrophages and hepatocytes requires ongoing protein synthesis. In contrast, we recently reported that CHX actually induces iNOS mRNA in rat vascular smooth muscle cells (VSM) (19). Additionally, the induction of iNOS mRNA by LPS is substantially potentiated by CHX in VSM (19).…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, we recently reported that CHX actually induces iNOS mRNA in rat vascular smooth muscle cells (VSM) (19). Additionally, the induction of iNOS mRNA by LPS is substantially potentiated by CHX in VSM (19). Thus, a fundamental difference appears to exist in the regulation of iNOS mRNA among cell types.…”
Section: Discussionmentioning
confidence: 85%
“…The frequent occurrence of cardiac disturbances during or after exposure to CO, such as increased frequency of anginal attacks, arrhythmia, and increased levels of cardiac enzymes, has led to a search for morphological changes that could be attributed to CO, especially because the myocardium has been shown to bind more CO than skeletal muscle [4,5]. There is a decreased oxidative phosphorylation [6,7] with a parallel decrease of heart rate, pulse pressure [8,9,10,11] and increased coronary blood flow [8,12] with a relative subendocardial underperfusion [13] whereby vasodilatation is the major response to CO hypoxia [14]. The cardiac electrical instability is not influenced by CO exposure in both normal and ischemic dog hearts, without any effect on coronary blood flow and platelet aggregation [15], a finding which apparently contrasts with other studies both in animals and in human coronary artery disease [12,16].…”
Section: Introductionmentioning
confidence: 99%